Diseño de un sistema contable para la asociación de desarrollo integral de mujeres de Pucayacu “Adimup” de la provincia de Cotopaxi, cantón la maná período enero-diciembre del 2008 - Ibáñez Esquivel, Nancy Teresa (2011)
Nowadays, the business world is developing lastly and this development is associated with the changes that appear in technology, the new requirements of information, the socio – cultural and economic exist in our environment. The Accounting is evolved into a more scientific and reasonable analysis, offering with precision every needed facts to organize an institution. The company’s accounting is done in a technical and scientific way, for this reason is necessary to develop Accounting Systems perfectly to determine the environment conditions. The verification of the hypothesis was carried out based in a logical method using the instruments applied to the members of “PWIDA”, representing them by graphics, bars and statistical representations in order to establish the conclusions and recommendations. The variables used were the scientific research and the accounting system to improve the actual situation of the company.